Psychosocial correlates of rehabilitation from stroke: a longitudinal study - Staccini, Laura <1982> (Alma Mater Studiorum - Università di Bologna, 2015)

(untitled)
The general aim of this dissertation was to uncover the association between psychosocial factors and rehabilitation outcome after stroke. METHOD. A sample of patients with stroke (n=40) and their caregivers (n=36) were assessed at admission to and six months after discharge from rehabilitation hospital, using the following instruments: Structured Clinical Interview for DSM-IV, structured interview based on Diagnostic Criteria for Psychosomatic Research, Symptom Questionnaire, Psychosocial Index, Psychological Well-Being Scales, and Family Assessment Device. 40 subjects from the general population underwent the same psychological assessment. In addition, patients' functional status was measured using the Functional Independence Measure. RESULTS. Stroke survivors reported lower education and higher alcohol consumption than controls. No significant differences emerged between the two groups in the prevalence of psychiatric diagnoses or psychosomatic syndromes, however patients reported significantly higher levels of anxiety, depression, somatic symptoms, and lower autonomy than controls. Caregivers reported significantly higher scores in anxiety, depression, and somatic symptoms compared to normative data, while no impairments emerged in psychological well-being and family functioning. At six-month follow-up, in patients a significant decrease in smoking habit and an increase in DSM diagnoses were reported. Both stroke survivors and caregivers showed significant reductions in anxiety, with patients displaying also a decrease in somatic symptoms, an increase in stress and a deterioration in quality of life. Significant deteriorations in several aspects of family functioning was perceived only by patients. An association between patients' functional recovery in the cognitive domain and family behavior control emerged. For caregivers, family functioning significantly predicted hostility and somatic symptoms were associated with family affective involvement. CONCLUSIONS. These data highlight the utility in the Italian setting of the adoption of a psychosocial assessment and a family-systems approach in stroke rehabilitation, in order to development interventions properly targeted to the characteristics of patients and their family members.